Law contra sociology: The critique of the social sciences, especially Durkheimian sociology, by Kelsen and Schmitt. (November 2017) - Terrier, Jean
This article explores the reception of Emile Durkheim in Germany at the beginning of the twentieth century. In recent years, the classical assumption according to which sociology is neatly organised in distinct national traditions has been challenged. This article further contributes to this challenge by analysing the case of two prominent German-speaking legal scholars, Hans Kelsen and Carl Schmitt. Despite major differences in their political and scientific outlook, both argued against the encroachments of the social sciences into the field of legal studies. This article shows how Kelsen mounted a polemic against Durkheim, on the basis of a first-hand knowledge of his writings. Kelsen believed that Durkheim committed several errors. In particular, he interpreted Durkheim's famous sentence according to which 'social facts must be treated as things' as a clear sign of a materialistic, deterministic and positivistic attitude which neglects the power of ideas and norms. Schmitt targeted sociology by way of a criticism not of Durkheim but of Léon Duguit, who had been inspired by Durkheim and pleaded for a collaboration between legal scholars and social scientists. According to Schmitt, a sociological approach to law amounts to a dangerous denial of the centrality of the state in politics.